Laboratory investigation of high-temperature functional characterization of organo-modified nanoclay-enhanced bitumen - Hazratullah Paktin; M. Kumar; V. Vinayaka Ram; Siksha Swaroopa Kar (Results in Engineering)
Functional properties are critical requirements for the efficacy of any modifiers used in bitumen modification. Recently, nanoclay has garnered significant attention as a pivotal option for improving bitumen performance. This research examines crucial functional attributes, including dispersion, phase separation at high temperatures, temperature susceptibility, and the potential aging resistivity of bitumen modified with organo-modified nanoclay (OMNC). Different percentages of OMNC (0 % to 8 % at a 2 % increment) were used by weight of control VG-30 bitumen. Scanning electron microscopy (SEM) was used as a conventional method for OMNC dispersion, while viscosity measurements and frequency sweep tests were conducted to indirectly assess the dispersion. Additionally, temperature susceptibility was evaluated through penetration index (PI) values. Conventionally applied softening point (SP) test and Multiple Stress Creep Recovery (MSCR) test data were used for phase separation purposes. SEM images, viscosity, and the Superpave rutting parameter (G*/sinδ) indicated that OMNC up to 8 % disperses well in the bitumen matrix. Further, the increment in softening point (ISP) was dropped from 4.6 °C to 2.5 °C with 8 % OMNC, while the aging index (AI) based upon shear modulus (G*) and phase angle (δ) were reduced from 2.4 to 1.7 and 2.9 to 1.1, respectively, at 80 °C, which revealed a constructive influence of OMNC on aging resistance. Moreover, the study assessed stability at high temperatures through SP and MSCR tests. Both SP and MSCR exhibited a satisfactorily steady nature of OMNC at elevated temperature storage conditions. Lastly, improved rutting performance was seen with addition of OMNC to bitumen binders.